Trilha interpretativa no ensino grupos botânicos nos anos finais do ensino fundamental - Francesquetto, Anelise (2024)
This text is based on the need to promote the teaching of Botany and environmental preservation in the final years of elementary school. Among the contents that botany covers, we have the five main plant groups: bryophytes, lycophytes, ferns, gymnosperms and angiosperms. These groups are extremely relevant to the understanding of plant biodiversity and its importance to the environment and society. This understanding leads to the formulation of the following research question: how can the use of interpretive trails as a teaching methodology help students develop greater knowledge about botanical groups and consequently generate awareness about the environmental issues that involve them? To this end, this work has as its main objective to develop, construct and apply a didactic sequence aimed at contemplating the theme of Botany with elementary school students - final years. The didactic sequence is based on the perspective of the Three Pedagogical Moments as announced by Delizoicov, Angotti and Pernambuco (2009), being structured in three moments: Initial Problematization, Knowledge Organization and Knowledge Application. The didactic sequence aims to allow the student to become the protagonist of the construction of his own knowledge based on a problem identified in his surroundings. As theoretical support, the study uses the work of Paulo Freire, bringing his core concepts that support the process of constructing the intended knowledge. The study was developed in a seventh-grade class at the São José Municipal Elementary School, located in the city of São José das Missões - RS. The research has a qualitative approach and uses a questionnaire and a logbook filled out by the teacher researcher as data collection instruments. This work contributed to the construction of significant knowledge about Botany, making the student the protagonist of this construction, starting from their previous knowledge and combining it with the scientific knowledge they saw during the didactic sequence and the completion of the interpretative trail. The educational product that accompanies this dissertation is an interpretative trail guide, which is free and open access, available for download (http://educapes.capes.gov.br/handle/capes/746294).